Changing the Shape of Watt-Ampere Characteristic of LEDs Based upon GaP ([lambda]=590 nm) Irradiated by Gamma-Quanta; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Gradoboev A. V. Aleksandr Vasilyevich (2019, 2019)
Title screen